The Archer and Aristotle’s Doctrine of the Mean - Koehn, Glen (Peitho. Examina Antiqua, 2012)
It is sometimes claimed that Aristotle’s doctrine of the Mean is false or unhelpful: moral virtues are not typically flanked by two opposing vices as he claimed. However, an explicit restatement of Aristotle’s view in terms of sufficiency for an objective reveals that the Mean is more widely applicable than has sometimes been alleged. Understood as a special case of sufficiency, it is essential to many judgments of right and wrong. I consider some objections by Rosalind Hursthouse to Aristotle’s theory and argue that they are based on a misunderstanding. However, there is indeed a tension in Aristotle’s view of goodness, hinted at in his claim that the good is "said in many ways".